2014
DOI: 10.1097/dbp.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parenting, Media Use, Cumulative Risk, and Children's Executive Functioning

Abstract: The study showed a complex pattern of associations between cumulative risk, parenting, and media exposure with EF during early childhood. Consistent with the American Academy of Pediatrics, these findings support the recommendation that background television should be turned off when a child is in the room and suggest that exposure to high-quality content across multiple media platforms may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 35 publications
3
136
1
10
Order By: Relevance
“…[16] Background TV is defined generally as TV to which the child is not paying overt attention, possibly because it is not child-oriented [7] or the child is engaged in another activity. Two recent studies reported that a child’s attention during play was disrupted in the presence of background TV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Background TV is defined generally as TV to which the child is not paying overt attention, possibly because it is not child-oriented [7] or the child is engaged in another activity. Two recent studies reported that a child’s attention during play was disrupted in the presence of background TV.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Furthermore, background TV exposure has been found to be associated with lower levels of self-regulation in preschool aged children. [6] Together, the evidence demonstrates a clear need for concern regarding the impact of background TV on the healthy development of young children.…”
Section: Introductionmentioning
confidence: 99%
“…71 Toddlers with socialemotional delays are more likely to be given a mobile device to calm them down, 72 73 found that the quality of parenting can modify associations between media use and child development: inappropriate content and inconsistent parenting had cumulative negative effects on low-income preschoolers' executive function, and warm parenting and educational content interacted to produce additive benefits.…”
Section: Are Certain Children or Families More Susceptible To These Rmentioning
confidence: 99%
“…A amostra parental em sete estudos foi mista, ou seja, composta por pais, mães, avós, cuidadores primários e responsáveis legais (SCHROEDER & KELLEY, 2009;SCHROEDER & KELLEY, 2010;ROSKAM et al,2014;LINEBARGER et al, 2014;CLARK & WOODWARD, 2015). Um estudou investigou apenas as mães (BERTHELSEN et al, 2017) Keywords: executive functions; parenting style; parenting practices; socioeconomic level; child; mother…”
Section: Parentalidadeunclassified
“…(BERTHELSEN et al, 2017;LINEBARGER et al, 2014;ROSKAM et al, 2014). de um discurso interno estruturado, que resulta em melhor autocontrole, monitoramento e elaboração de estratégias de planejamento mais efetivas (ZELAZO et al, 2003;SOKOL et al, 2010).…”
Section: Crianças De 8-9 Anosunclassified